Evaluation of Antioxidant Potential and Total Phenolic Content of Leucodon sciuroides (Hedw.) Schwager. - BENEK, Atakan; CANLI, Kerem; Altuner, Ergin Murat (Zenodo, 2025)
Bryophytes have been attracting increasing attention as potential sources of natural bioactive  compounds due to their diverse ecological adaptations and secondary metabolite profiles. In this  study, the antioxidant potential and total phenolic content of the moss species Leucodon sciuroides  (Hedw.) Schwägr. were evaluated. Antioxidant activity was assessed using the 2,2 diphenyl-1 picrylhydrazyl (DPPH) radical scavenging assay and the cupric ion reducing antioxidant capacity  (CUPRAC) method, while phenolic content was determined by total phenolic content analysis  The DPPH assay was applied at eight different concentrations ranging from 0.0078125 to 1 mg/mL. Scavenging activity increased in a concentration-dependent manner, reaching a maximum  inhibition of 40.48% at 1 mg/mL. The EC50 value, representing the concentration required to  scavenge 50% of DPPH radicals, was calculated as 5.00 mg/mL, indicating a moderate level of  antioxidant capacity.  In the CUPRAC method, absorbance values expressed in terms of ascorbic acid equivalents (AAE, mM) increased with rising concentrations. At concentrations of 1.0, 2.5, 5.0, 7.5, and 10.0 mg/mL, the AAE values were determined as 0.258±0.01, 0.540±0.02, 0.722±0.02,0.889±0.03, and 0.940±0.07, respectively. These results demonstrate the extract's ability to reduce Cu (II) to Cu (I), thus confirming its antioxidant power. The total phenolic content was determined in terms of gallic acid equivalents. As a result of the analysis, the total phenolic content of L. sciuroides was found to be 51.18±4.28 mg GAE/g extract. This indicates that phenolic compounds contribute significantly to the antioxidant activity observed.  In conclusion, L. sciuroides exhibits measurable antioxidant activity in terms of both radical  scavenging and reducing power and contains a notable amount of phenolic compounds. These  findings provide a scientific basis for the evaluation of mosses as natural antioxidant sources for  potential use in pharmaceutical or nutraceutical applications.